(3aJM GdeYjf TQM bQI GdYjf HegeGJ GdOjfs - (3GdedjHGQj, Rjf GdOjf Hf YHO GdYRjR Hf Rjf GdOjf, J (B987 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdaJGM GdLhGO GdeYjf Ydi GdJabg aj GdOjf ef GNJGQg ef GdYHGO hHYO agPG TQM eajO Ydi cJGHj gPG GdeSei HbQI GdYjf HegeGJ GdOjf jHjf GdeQGO hdjJee GdeaGO hjMUd GdebGUO hjHQR GdahGFO hSejJg HaJM GdeYjf s
(3BNQgG (B:s
(3hNGeSgG (B: (3UdGI Ydi GdfHj Udi Gddg Ydjg hSde HYO JcHjQg KGfjI Cj YbHgG adG jLRA aj ZjQgG hjfOH Ve GdSdGe ddUdGI hGdOYGA ddeDefjf hGdeDefGJ YbHgG hGdMeO ddg bHdgG , hSGOSgG (B: (3OYGA ddejJ HNUhUg hdh WadGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 64s
(3eYLe GdeDdajf (B3 / 741s
(3NdGUI GdCKQ (B2 / 189s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdTGaYjs